Estudo espectroscópico de materiais: a mútipla aplicabilidade da espectroscopia Raman na caracterização de aminoácidos, molibidato e tungstato de sódio, e óxidos nanomoldados - Lima, Cleânio da Luz (2011)
Structure determination of aminoacid (C5H9NO4), tungstate (Na2WO4) and molybdate (Na2MoO4), and MOx nanostructureed oxides was performed through Raman spectroscopy. L-glutamic acid was investigated by Raman spectroscopy with the aim of evaluating the effect of the hydrostatic pressure on their structural and vibrational properties. The nanocrystalline samples were obtained by slow evaporation method; and two polymorphic phases were produced. To identify the abovementioned phases, X-ray diffraction (XRD), thermal analysis (DSC), infrared spectra (FT-IR) and Raman spectroscopy experiments were performed. The latter was decisive to distinguish the two phases formed, and was complementary to XRD. When high pressures were applied, modifications in the L-glutamic acid structure were observed. Such a modification was due to vibrational and changes in the wavenumber versus pressure curves. These modifications evidenced that the β-phase of the crystal had four structural phase transitions from room pressure to 21.5 GPa; for α-phase crystal, there structural phase transitions from room pressure to 7.5 GPa. Decompression to room pressure provided the restored original spectra, which indicating that the phase transitions were reversible to the aforesaid phases. Variation of the temperature of the polycrystalline Na2MoO4 and Na2WO4 was performed to obtain information about the structural change occurred the solids. Cubic phase stability of the Na2MoO4 and Na2WO4 was verified and these studies indicated that the crystals maintained the cubic phase in the 8- 823 K and 15 – 773 K range for Na2MoO4 and Na2WO4 crystals, respectively; a first order transition phase was shown through the Raman modes behavior: the splitting of the new modes appeared below to 100 cm-1. These transitions were due to the disorders of MoO4 and WO4 sites from Na2MoO4 and Na2WO4 structure, respectively. The structure determination of nanostructured oxides (monoxides and binary oxides) was investigated by Raman spectroscopy. Nanoparticles mode of CeO2, ZrO2 and TiO2 as well as that of CeO2-ZrO2 and Ce0.08Zr0.2O2 were obtained. XRD analysis, textural and surface properties and Raman spectroscopy, being the latter responsible for a deeper understanding of the structural properties of the nanoparticles and nanostructure when applied as catalysts for glycerol dehydration to acrolein and 1-hydroxyacetone the solids were actives, and actively was related to the solids structure.